Read, From Tsar To Soviets - The Russian People And Their Revolution, 1917-21 - Wilcoxson, Elizabeth (Teaching History: A Journal of Methods, 1997)
Christopher Read states in his introduction that his purpose in writing this book is to examine the role of ordinary Russians in the 1917 revolution and its aftermath. He adds that "the tragedy of the revolution lies in the Bolsheviks' failure to recognize the real revolution of the time and instead to pursue their own highly structured presuppositions about what the revolution should have been like and what the chief actors should have been doing." To develop his thesis, Read takes us through a chronology of the revolutionary era in Russia.